Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1471-4159.1993.tb03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Monitoring of 3,4‐Dihydroxyphenylalanine Accumulation After Decarboxylase Inhibition: A Means to Estimate In Vivo Changes in Tyrosine Hydroxylase Activity of the Rat Locus Ceruleus

Abstract: An on-line microdialysis approach was developed to estimate changes in tyrosine hydroxylase activity in the locus ceruleus noradrenergic neurons of anesthetized rats by measuring the 3,4-dihydroxyphenylalanine (DOPA) accumulation in the extracellular fluid during perfusion of a n aromatic amino acid decarboxylase inhibitor through a dialysis probe. The aromatic amino acid decarboxylase inhibitor used was difluoromethyl-DOPA, which was shown to be more stable than NSD 10 15 or Ro 4-4602 in the perfusion fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Accumulation of L-DOPA after inhibition of AADC was used to isolate the in vivo TH function from other variables such as DOPA decarboxylation, dopamine uptake, and metabolism of dopamine by subsequent enzymatic steps (Carlsson et al, 1972;Westerink et al, 1990;Robert et al, 1993). Our data demonstrate that in the absence of its metabolism, L-DOPA accumulates in the striatum of rats with PFTHGC grafts, supporting the idea that TH function is enhanced by this genetic modification.…”
Section: Discussionsupporting
confidence: 71%
“…Accumulation of L-DOPA after inhibition of AADC was used to isolate the in vivo TH function from other variables such as DOPA decarboxylation, dopamine uptake, and metabolism of dopamine by subsequent enzymatic steps (Carlsson et al, 1972;Westerink et al, 1990;Robert et al, 1993). Our data demonstrate that in the absence of its metabolism, L-DOPA accumulates in the striatum of rats with PFTHGC grafts, supporting the idea that TH function is enhanced by this genetic modification.…”
Section: Discussionsupporting
confidence: 71%
“…Conversely, the perfusion of 3 mmol/L NSD1015 induced the highest levels of L-DOPA with reduced variability between animals. Under these conditions, however, the inhibitor or its metabolites observed in the chromatogram [13,19] masked the identification of both DOPAC and HVA.…”
Section: Microdialysis Sessionsmentioning
confidence: 87%
“…Nevertheless, numerous studies have shown that extracellular concentrations of L-DOPA are strongly correlated with TH activity when it is modified by pharmacological agents. Thus, the general consensus is that this method is valid as an in vivo measure of TH activity [13,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation